Diagnostic Efficacy of Troponin – I qualitative Rapid test in Sudden Cardiac Deaths - Kumar , P P; Sabale , P R; Amonkar , G P (Journal of Indian Academy of Forensic Medicine, 2023)
Everyone knows by conducting autopsy cause of sudden unexpected death can be established. However due to limitations of staff, budget  and time it forces the autopsy surgeon to triage the cases. Out of which sudden cardiac deaths because of acute myocardial infarction  constitute a significant percentage of caseload. When an autopsy is performed, there may be significant cardiovascular disease but there  will be no gross or histological evidence of an acute myocardial infarct unless the patient survived for few hours. Troponin I (cTnI) done  using peripheral blood was sampled percutaneously before conducting internal examination of each of 60 autopsies. The rapid assay  result, histopathological results were tabulated and subsequently correlated. Out of 30 cases all showed positive result but in 30 controls 11  showed false positive results and 19 showed negative results. This result was statistically significant according to the chi-square test. The  sensitivity of this assay in detecting cardiac-related death was 100%, with a specificity of 63.33%. In the appropriate setting, this rapid  assay for cTnI can provide valuable data supportive of a cardiac-related death. This inexpensive test may best be used in triaging sudden  deaths in persons and may optimize the use of the time and resources of the autopsy pathologist.
Keywords: Troponin – I; Acute MI; Sudden deaths